Penerapan Fuzzy Logic Pada Sistem Pintu Otomatis Menggunakan Sidik Jari Berbasis Arduinno Uno - Rahmad, Iwan Fitrianto; Lubis, Juanda Hakim; Ummi, Khairul; Akbar, M. Ridho (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
The door security system using fingerprint is one of the many systems that is often used to add a level of security to school, home and other doors. The door system uses fingerprints as a medium to read or identify so that the door can be opened. Automatic doors with a fingerprint recognition system are a modern solution for securing access to various locations. The implementation of Fuzzy Logic in this tool is used to provide a delay time of 3 seconds in the open state based on the number of fingerprints attached. Arduino Uno functions as the main controller that integrates the fingerprint module and door actuator. The result of this research is a door security system tool that applies a fuzzy logic algorithm and includes a hardware and software design process, including integration of electronic components and development of a fingerprint verification algorithm. Implementation The experimental method is used to test the reliability of the system in user recognition and access. Experimental results show that the system can identify users with high accuracy and provide a fast response in operating the automatic door. The practical contribution of this research is the development of automatic door technology that can be applied in various contexts to increase user safety and comfort.